DEVELOPMENT OF DYNAMIC CAPABILITY AS A STRATEGY TO IMPROVE ORGANIZATIONAL ECONOMIC PERFORMANCE IN THE ERA OF DIGITAL DISRUPTION - Susan Kristinawati; Gofur Ahmad; M. Irfan Tarmizi; Yatimin (ZILLZELL MEDIA PRIMA, 2026)
Digital disruption requires organizations to adapt quickly and sustainably in order to maintain economic performance. This research aims to analyze the influence of dynamic capability on organizational economic performance in the era of digital disruption. The study uses a quantitative approach with the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. Data was collected through questionnaires from 150 respondents from organizations that have adopted digital technology. Dynamic capability is measured through three dimensions, namely sensing, seizing, and transforming, while organizational economic performance is measured based on profitability, growth, and efficiency. The results of the SEM-PLS analysis show that all dimensions of dynamic capability have a positive and significant effect on the economic performance of the organization. The transforming dimension has the most dominant influence over sensing and seizing. The value of the determination coefficient (R²) of 0.58 indicates that dynamic capability is able to explain 58% of the variation in the organization's economic performance. These findings confirm that the development of dynamic capabilities is an important strategy in improving organizational economic performance in the era of digital disruption.